Strindberg : a life - Prideaux, Sue (Yale University Press, 2012)
Novelist, satirist, poet, photographer, painter, alchemist, and hellraiser--August Strindberg was all these, and yet he is principally known, in Arthur Miller's words, as "the mad inventor of modern theater" who led playwriting out of the polite drawing room into the snakepit of psychological warfare. This biography, supported by extensive new research, describes the eventful and complicated life of one of the great literary figures in world literature. Sue Prideaux organizes Strindberg's story into a gripping and highly readable narrative that both illuminates his work and restores humor and humanity to a man often shrugged off as too difficult. Best known for his play Miss Julie, Strindberg wrote sixty other plays, three books of poetry, eighteen novels, and nine autobiographies. Even more than most, Strindberg is a writer whose life sheds invaluable light on his work. Prideaux explores Strindberg's many art-life connections, revealing for the first time the originals who inspired the characters of Miss Julie and her servant Jean, the bizarre circumstances in which the play was written, and the real suicide that inspired the shattering ending of the play. Recounting the playwright's journey through the "real" world as well as the world of belief and ideas, Prideaux marks the centenary of Strindberg's death in 1912 with a biography worthy of the man who laid the foundation for Western drama through the twentieth century and even into the twenty-first.